The Study of Quality of the River Pandayangan in His Review of the Factors of Physical-Chemical - Manalu, Bunga Nasib; Harahap, Arman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The river is one of the forms of the aquatic ecosystem is open, which is also prone to the existence of a pollution.Pollution that occurs in a river is usually caused by environmental conditions and human activities around the river.The river water Pandayangan is one of the rivers that are widely used by the local community for a variety of activities, namely as a tourist attraction, bathing, washing, and others. This research is a descriptive research that aims to determine the water quality of the river in physics and chemistry of the location of the research based on the raw water quality. Research conducted at three locations and sampling the water for the third observation stations do the measurement of physical parameters such as Temperature, Color, and Turbidity while the chemical parameters include pH, BOD, Ammonia, Nitrite, Organic Number, Alkaliniti and Asiditi. Based on the results of testing the physical and chemical parameters then be concluded that the water quality of the river Pandayangan still meet the quality standards of water quality class B or raw water.